Electric Field Assisted Microfluidic Platform for Generation of Tailorable Porous Microbeads as Cell Carriers for Tissue Engineering. (25th March 2018) - Costantini, Marco; Guzowski, Jan; Żuk, Paweł J.; Mozetic, Pamela; De Panfilis, Simone; Jaroszewicz, Jakub; Heljak, Marcin; Massimi, Mara; Pierron, Maxime; Trombetta, Marcella; Dentini, Mariella; Święszkowski, Wojciech; et al.
Abstract: Injection of cell‐laden scaffolds in the form of mesoscopic particles directly to the site of treatment is one of the most promising approaches to tissue regeneration. Here, a novel and highly efficient method is presented for preparation of porous microbeads of tailorable dimensions (in the range ≈300–1500 mm) and with a uniform and fully interconnected internal porous texture. The method starts with generation of a monodisperse oil‐in‐water emulsion inside a flow‐focusing microfluidic device. This emulsion is later broken‐up, with the use of electric field, into mesoscopic double droplets, that in turn serve as a template for the porous microbeads. By tuning the amplitude and frequency of the electric pulses, the template droplets and the resulting porous bead scaffolds are precisely produced. Furthermore, a model of pulsed electrodripping is proposed that predicts the size of the template droplets as a function of the applied voltage. To prove the potential of the porous microbeads as cell carries, they are tested with human mesenchymal stem cells and hepatic cells, with their viability and degree of microbead colonization being monitored. Finally, the presented porous microbeads are benchmarked against conventional microparticles with nonhomogenous internal texture, revealing their superior performance. Abstract : Monodisperse porous beads with controlled internal porous texture are fabricated with high reproducibility and efficiency by coupling a microfluidic oil‐in‐water emulsion generator with a secondary break‐up triggered by a pulsed electric field. The so‐produced porous beads demonstrate excellent performance as cell carriers.